Exploring Collaborative Approaches in Literature Education: Fostering Creative Expression and Student Engagement through Adaptation of â€œAn Inspector Callsâ€ - Jayapalan, Evelyn; Theventhiran, Daviena; Shreevaani, Sadhana; Selvraju, Joycelyn; Seigar, Iveena Sharveeni; Velautham, Anjali (Universitas Pendidikan Mandalika, 2024)
Encouraging undergraduate students to engage in literary interpretation fosters creative thinking and enables them to perceive contexts in diverse and meaningful ways. Collaborative efforts among students to develop a unified interpretation of a new plot derived from the original storyline can liberate them from rigid thought patterns, allowing for greater expression of creativity in literary appreciation. Â This qualitative study aims to explore the undergraduatesâ€™ creativity and ability through conceptualization and dramatization by demonstrating their appreciation with practical application.This research is a descriptive research employing a qualitative approach. The study involves 14 TESL undergraduates from a Malaysian higher education institution, second and third-year students created a new interpretation of a plot for Part 2 of 'An Inspector Calls,' drawing inspiration from the Freytag Pyramid. This study utilizes content analysis of the new plot structure and an observation checklist for documenting the staging process.. The findings of the study reveal the TESL undergraduates' proficiency in appreciating the essence of